PERANCANGAN KAMPANYE SEBAGAI MEDIA PEMBELAJARAN AKSARA SUNDA DI KALANGAN REMAJA SMP KOTA SUKABUMI - Safitri, Sarah Hastawati; Firdaus, Rizki Alfiansyah (Universitas Mercu Buana, 2022)
This final task helps teachers in providing learning materials Sundanese Script. The purpose of the designer of the learning media of Sundanese Script is to commit the effort to preserve Sundanese Script in the area of Sukabumi, in particular the adolescent level. With video-based lotion-based learning can feature an attractive learning script, informative, and is not boring so that it can attract the interest of students in studying sundanese characters.This final task was compiled using a descriptive qualitative method. The learning media in this campaign are in the form of motion graphics videos, x- banners, tote bags, bucket hats, offline and online posters, key chains, and t- shirts. Therefore, the designers of the learning media of sundanese script are the most effective way in the preservation campaign of sundanese characters among junior high SMP.